Characterisation of mulloway Argyrosomus japonicus advertisement sounds - Parsons, Miles; McCauley, Robert; Mackie, Michael (Australian Acoustical Society, 2013)
Increasingly, fishes are reported as using acoustic variations in calls for different environmental and social contexts. However, to understand call functions and their associated behaviours it is first necessary to separate and characterise the species call types. During the Austral summer, mulloway (Argyrosomus japonicus), a vocal sciaenid, aggregates to spawn in the lower regions of the Swan River, Western Australia. In situ A. japonicus calls recorded here exhibited call spectral peak frequencies between 175 and 350 Hz and pulse repetition rate of 59 Hz. These swimbladder driven calls were categorised into; short grunts of 1-6 pulses (‘Bup’), more predominant as the aggregation forms and separates; long grunts comprising 11-32 pulses (‘Baarp’), most prominent in the hours after sunset; and a series of short calls comprising 1-5 pulses (‘Thup’) that increase sharply in call rate over a period of tens of seconds. This last category was observed only once or twice each evening. The second category was divided into several types of call where a single audible tone can also be broken into twoor more parts, often preceded by one or more short ‘Bups’ (for example, ‘Bup-bup-baarp’).